PERANCANGAN SISTEM PENGENDALIAN KUALITAS PRODUKSI GENTENG BETON DENGAN PENDEKATAN METODE FAULT TREE ANALYSIS, FAILURE MODE AND EFFECT ANALYSIS UNTUK MENINGKATKAN KUALITAS PRODUK - Mahyar; Supriyadi, Edy (EKOBISMAN : JURNAL EKONOMI BISNIS MANAJEMEN, 2020)
This research was conducted to design a quality control system for concrete tile products. The purpose of this study is to reduce the defect rate of concrete tile products at PT CTC. Defective products that occur tend to increase at 5.49% for one year with a total production of 6,529,735 tiles. Product defects that occur are caused by broken, broken, cracked, porous, curved, dry and faded paint. By looking at the data, the company needs a system that needs to be implemented to reduce the level of product defects that occur by conducting a Fault Tree Analysis (FTA) to find the root causes that cause defects in the product. Next, we call the Failure Mode and Effect Analysis (FMEA) analysis to find the completion steps. The results of the FMEA analysis showed that the most dominant type of defect was due to rupture with a value of RPN = 513 caused by human factors. After the improvement implementation and anova testing were performed, it showed a significant difference before and after the repair with a mean value of 1.6.